2017
DOI: 10.1093/tropej/fmx092
|View full text |Cite
|
Sign up to set email alerts
|

Global Health Journal Club: Is Honey Effective as a Treatment for Chemotherapy-induced Mucositis in Paediatric Oncology Patients?

Abstract: Oral mucositis (OM) is an inflammatory response of mucosal epithelium to the cytotoxic effects of chemotherapy and radiotherapy causing severe oral pain and ulceration, which may complicate the management of cancer. The Mucositis Prevention Guideline Development Group has developed an international guideline for the prevention of mucositis in children receiving treatment for cancer or undergoing haematopoietic stem cell transplantation. Evidence-based preventative strategies include cryotherapy, low-level ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
(7 reference statements)
0
10
0
1
Order By: Relevance
“…Friend et al specifically examined pediatric trials and identified 4 trials 62 , 71 , 77 , 79 with grade C evidence that honey was effective as a preventative and adjunctive therapy for chemotherapy-induced oral mucositis in children. 121 Honey was found to reduce the frequency, duration, and stage of chemotherapy-induced mucositis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Friend et al specifically examined pediatric trials and identified 4 trials 62 , 71 , 77 , 79 with grade C evidence that honey was effective as a preventative and adjunctive therapy for chemotherapy-induced oral mucositis in children. 121 Honey was found to reduce the frequency, duration, and stage of chemotherapy-induced mucositis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent interventions have continued to explore and to further build the scientific and clinical understanding of oral and intestinal mucositis preventative and treatment options that may be available to clinicians and patients. 13 , 112 , 121 , 133 The prevention and treatment of oral and intestinal mucositis that seeks to decrease the risk of formation and/or progression of these deleterious sequela of chemoradiotherapy regimens are important factors that impinge on patient quality of life and clinical decisions relevant to treatment. While it is acknowledged that oral and intestinal mucositis represent significant burdens of antineoplasitic therapies, the implementation of adjunctive treatments still remain a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…There is a systematic review on honey for the treatment of chemotherapy-induced mucositis in paediatric oncology patients [14]. It summarizes four papers on the topic and provides Grade C evidence that honey is effective as a preventative and therapeutic measure in paediatric oncology patients.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis indicates that honey can effectively reduce the incidence of chemotherapy and radiotherapy-induced oral mucositis (Xu et al, 2016 ). Further clinical evidence demonstrates its effectiveness as a preventative and therapeutic measure for chemotherapy-associated oral mucositis in pediatric oncology patients (Friend et al, 2018 ). There is potential interaction between oral microenvironment and mucositis development.…”
Section: Prevention Of Oral Mucositis Partly By Reducing Oxidative Stmentioning
confidence: 99%